Relative clauses in the Secret History of the Mongols - Suying Hsiao (Mongolian Studies, 2023)
This paper investigates relative clauses in the Secret History of the Mongols. Corpora of SHM compiled by the author were used and all relative clauses were tagged. Most cases of the relative clauses in SHM are pre-nominal or headless. Some relative clauses, however, appear after the head noun and occur in the sequence of “(Numeral, Determiner) Head RelativeClause”. We have also found some cases in which both the head and the relative clause bare the same Case marking. These clauses are nonrestrictive relative clauses, and their behavior in Case marking supports the analysis of treating a nonrestrictive relative clause as an appositional clause of the head noun. To sum up, there are two types of [...Head [Relative Clause]] sequences in SHM. One is the regular type in which the whole noun phrase takes one Case. In the other type the head noun and the relative clause are both Case-marked with the same Case, showing some sort of concordance. The former type is restrictive and the latter is appositional and non-restrictive.